PEARLS MONITORING SYSTEM PADA CREDIT UNION DI KOTA MALANG - Ninik Sulistyani (Jurnal Universitas Paramadina, 2014)
This research aims to analyze the financial performance usingPEARLS method in the credit unions in Malang in the years 2008—2012.The sources of data in this research are secondary data, such as balancesheet and income statement of all the credit unions financial statement inMalang in the years 2008—2012. The population in this research are thecredit unions which are listed in the Credit Union Counselling Office(CUCO)-Indonesia. The samples are the credit unions that have a centraloffice in Malang, incorporated and registered in the Credit Union Centre ofEast Java. The data analysis techniques are the PEARLS method and Trendanalysis technique. The results of this research show that most of thefinancial performance of the credit unions in Malang as measured byPEARLS method in the years 2008—2012 are not in a good condition butRaya Credit Union has the best average financial performance are in the last5 years. The financial performances of Setaman Credit Union, Raya CreditUnion, and Kosayu Credit Union tend to rise in the last 5 years. Thefinancial performance of the Bimatera Credit Union tend to fall in the last 5years and the Abdi Sesama Credit Union financial performance remainsstable in the last 5 years. The statements of financial performance that arenot good in the last 5 years can be used as the consideration for the CreditUnion management to make a decision for the development of Credit Unionin the future.